INSTILLING RELIGIOUS MODERATION IN PROSPECTIVE ELEMENTARY SCHOOL TEACHERS AS AN EFFORT TO STRENGTHEN MULTICULTURALISM - Endang Sri Maruti (Proceeding International Seminar of Islamic Studies, 2023)
This research seeks to describe the form of instilling religious moderation in elementary school students in Madiun City as an effort to strengthen multiculturalism. This research is a descriptive qualitative type using exposure narratively and verbally. As for data collection using ethnographic techniques, namely observation, interviews, recording, and recording of PGSD students at the University of PGRI Madiun. Data were analyzed with a triangulation model. The results of the study show that religious moderation as a view that does not matter whether a religion is right or wrong needs to be instilled in PGSD students as prospective elementary school teachers in an effort to create a multicultural Indonesian nation.